Die monetar̈e Bewertung von Naturguẗern zwischen ok̈onomischer Theorie und politischer Umsetzung; Monetary valuation of the natural environment - economic theory and application in environmental policy - Ulrich Hampicke (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– During the past 15 or so years, a considerable number of valuation studies have been published in German language concerning nature conservation mostly in the agrarian countryside, using the Contingent Valuation Method (CVM). These are documented here and briefly commented on. In the sequel, well-known objections in the literature against this method are discussed and rejected or at least attenuated, thereby referring to more comprehensive literature. Upon careful design, the results from CVM studies bear closer examination as to their reliability. It seems doubtful, however, and must even be regarded as refuted in some special cases that their very objective, as formulated from a rigorous microeconomic position, is achieved, that is the disclosure of the Compensating Variation (VC) or Equivalent Variation (EV), respectively. Respondents' statements are influenced both by their experience in achieving a consumer surplus in everyday purchases and - more importantly - by normative, ethical, distributive and genuine political aspects. Intuitively, respondents realise the societal nature of the respective problems and are reluctant to communicate exclusively in individualistic terms of modern utility theory. It is argued that no adverse consequences ensue from this finding when CVM results are practically applied for the sake of improving economic allocation. Nature conservation policy should be more oriented towards CVM results rather than depend on the influence of political pressure groups.
Keywords: 330; Naturschutz; Natürliche Ressourcen; Zahlungsbereitschaftsanalyse; Kompensationsmaßnahme; Deutschland